2010
DOI: 10.1186/1471-2164-11-701
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation in glioblastoma: impact on gene expression and clinical outcome

Abstract: BackgroundChanges in promoter DNA methylation pattern of genes involved in key biological pathways have been reported in glioblastoma. Genome-wide assessments of DNA methylation levels are now required to decipher the epigenetic events involved in the aggressive phenotype of glioblastoma, and to guide new treatment strategies.ResultsWe performed a whole-genome integrative analysis of methylation and gene expression profiles in 40 newly diagnosed glioblastoma patients. We also screened for associations between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
158
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 181 publications
(170 citation statements)
references
References 42 publications
11
158
0
1
Order By: Relevance
“…Further, Etcheverry et al has performed a wholegenome integrative analysis of methylation and gene expression profiles on GBM samples and found that the Sox10 promoter contains two hypermethylated CpG sites which are related to shorter survival. However, shorter survival time is correlated with low-expression of Sox10 in the GBM samples (Etcheverry, et al, 2010), which fits with the expression data that Sox10 is expressed to a higher extent in low grade brain tumours. We and others have not found any expression of Sox10 in medulloblastoma (Ferletta, et al, 2007;Gershon, et al, 2005).…”
supporting
confidence: 86%
“…Further, Etcheverry et al has performed a wholegenome integrative analysis of methylation and gene expression profiles on GBM samples and found that the Sox10 promoter contains two hypermethylated CpG sites which are related to shorter survival. However, shorter survival time is correlated with low-expression of Sox10 in the GBM samples (Etcheverry, et al, 2010), which fits with the expression data that Sox10 is expressed to a higher extent in low grade brain tumours. We and others have not found any expression of Sox10 in medulloblastoma (Ferletta, et al, 2007;Gershon, et al, 2005).…”
supporting
confidence: 86%
“…Yamashita et al examined methylation-silenced genes in gastric cancer and revealed that the TBX3 promoter is methylated in at least one primary gastric cancer, but not normal gastric mucosa (75). TBX3 methylation was subsequently revealed to be associated with a significantly lowered survival rate in a cohort of glioblastoma patients (76). Following this, White-al Habeeb et al demonstrated that TBX3 is differentially methylated in Gleason score (GS) 8 vs GS6 prostate cancer tumour samples, with increased methylation occurring in the more aggressive GS8 samples (77).…”
Section: The Tumour Suppressor Role Of Tbx3mentioning
confidence: 99%
“…These compounds have been approved by the FDA as treatments for leukemia and myelodysplastic miR-29b [80] Promote cell differentiation in muscle and tumours miR-7 [81] syndromes [103]. DNA methylation also plays an important role in glioblastoma [104] and these compounds are now also under investigation as possible therapies for these cancers. Thus, treatment of glioma cells with 5-aza-dC was able to reactivate the expression of the brain angiogenesis inhibitor (BAI1), which is normally silenced in gliomas, by recruitment of the methyl-CpG-binding domain protein 2 (MBD2) to the hypermethylated BAI1 promoter [105].…”
Section: Small Moleculesmentioning
confidence: 99%